Website-Based Library Inventory Information System at SMAIT Putri Al Hanif - Winda Arianti; Muhamad Riyan Maulana (PT. Altaf Publishing Corp, 2024)
Library inventory management at SMAIT Putri Al Hanif is currently still done manually using a book recording system which is sometimes ineffective and inefficient. The difficulty of coordination between teachers and students also makes book management more complicated. Therefore, this research aims to design and implement a website-based library inventory information system at SMAIT Putri Al Hanif. The development method chosen is the waterfall method, which involves the stages of needs analysis, system design, implementation, testing, and maintenance. In the analysis stage, information searches related to the system to be developed and collection of inventory data are carried out. The system design stage includes data structure, software architecture, and programme appearance. Implementation involves translating the design into a programming language and creating a database. This web-based application has features such as user login, Home menu, menu to view book loan information, menu to view book return information, and user data. Testing is done using the Black box Testing method to ensure compliance with functional specifications. The results show that this application can facilitate inventory management, increase productivity, and facilitate coordination between departments. The result is a website-based library inventory information system that has been successfully implemented at SMAIT Putri Al Hanif, contributing to facilitating the recording, reviewing, and data collection of books in the library.